Para além do papel da casa: uma avaliação da implementação da política de regularização fundiária urbana na comunidade de Marrocos na ZEIS do Bom Jardim - Gois, Arilena Nobre (2024)
The objective of this study is to evaluate the implementation of the urban land regularization policy, investigating its application in the Marrocos community, located in the Special Area of Social Interest (ZEIS) in Bom Jardim, Fortaleza/CE. The policy has as its legal framework Federal No. 13.465/2017, which sets national guidelines, regulated and supervised by state and municipal authorities. The study investigated the right to housing and the sense of belonging to the place, considering the principles of private property and its social function. The research highlighted the evolution of the concept of private property over time and proposed to discuss the right to property in the context of land regularization policy, analyzing the factors that condition it. Federal Law No. 13,465/2017, which deals with urban land regularization, and Municipal Law No. 334/2020 were considered as regulatory frameworks. The adopted methodology included an analysis of these legal frameworks, along with historical plans, trajectories, and official publications from relevant institutional and research bodies. As for the methodological procedures, bibliographic and documentary research was sought, in addition to the application of a semi-structured research form, in order to build the institutional trajectory. The work is structured based on a qualitative approach, with occasional quantitative input, based on the paradigm of in-depth evaluation, highlighting some areas, such as: i) Content analysis, which seeks to contextualize the normative and documentary frameworks of the policy, in addition to its conceptual bases. ii) Context analysis, incorporating data collected from the research. iii) Institutional trajectory of the policy, through narratives of actors who have acted in the implementation of the policy from its creation to the present day. iv) Territorial spectrum/temporality, through the comparison of the objective of the policy with the local specificity and its historicity. (RODRIGUES, 2016). The approach proposed by Rodrigues is complemented by Lejano's experiential evaluation perspective, which emphasizes the experience and assessment of individuals affected by the urban land regularization policy. In this regard, the study aimed to understand the perceptions, feelings, and experiences of individuals directly involved in or impacted by this public policy. The study concludes that, although the urban land regularization policy has made progress in the Marrocos community, there are still areas in need of improvement, particularly in essential infrastructure such as basic sanitation and electricity supply. In this context, greater attention to the public services provided to the local population is crucial.